ANALISIS KEKALAHAN PASANGAN SOEMARMO-ZUBER DALAM PILKADA KOTA SEMARANG TAHUN 2015 - Hanifia Yunastiti; Turtiantoro . (Journal of Politic and Government Studies, 2018)
Soemarmo is the former Semarang City mayor elected in 2015. In his time, Soemarmo was involved in a law case forcing him to be imprisoned and surrender his position to Hendar Prihadi. In the 2015 Semarang mayoral election, Soemarmo once more submitted himself together with PKB and PKS (supporting political parties), and competed his former vice mayor, Hendar Prihadi. Despites his previous law case, he still had a high popularity among Semarang citizen. This proved by his consistency to be in the second place in every survey. In addition, the political party coalition supporting Soemarmo was considered to be a new coalition in Semarang mayoral election. Based on these, this research has objective to find out the factors causing the defeat of Soemarmo-Zuber pairs in the 2015 Semarang Mayoral Election. The type of this study is a descriptive study through qualitative approach. The data sources were gained from interview of some resources and documents related to this research. The data compiling technique used in this study is by using interview and analysis of document. Based on the research, it is known that factors causing the defeat of Soemarmo-Zuber are the supporting party machine, the figure of candidates, the winning strategy, and the negative campaign. The supporting party machine of Soemarmo-Zuber was not effective since PKS and PKB (supporting parties) were not suitable to each other in the aspect of religion value and party ideology. Moreover, PKS and PKB coalition was a small coalition in the 2015 Semarang Mayoral Election. Looking at the figure aspect, Soemarmo is quite popular for Semarang citizens. However, his negative image caused by his previous case covers his own quality. Talking about his vice, Zuber is not a popular figure for Semarang citizens. In addition, winning strategy used was not effective since their supporting party machine and coalition was not effective as well, not to mention their limited campaign fund. To add insult to injury, negative campaign from their opposition also helped to make Soemarmo’s image get worse. Keywords: Defeat, Party Machine, Figure, Winning Strategy, Negative Campaign